2016
DOI: 10.3928/00485713-20160506-01
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems and Disorders in Patients with Anxiety Disorders

Abstract: Anxiety and its disorders cause distress that interferes with sleep and wakefulness. Insomnia appears to be the most common sleep disturbance associated with anxiety disorders. Nocturnal enuresis and sleep terrors tend to be more common in childhood anxiety disorders, such as separation anxiety disorder and selective mutism. Poor sleep quality is seen in adults with anxiety disorders such as specific phobia, social phobia, panic disorder, and generalized anxiety disorder. Objective data obtained from polysomno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…High perceived stress, psychological distress, anxiety and depression are significant predictors of poor sleep quality and persistent insomnia [ 40 , 41 ] and can contribute to insomnia-related hyperarousal thus perpetuating chronic insomnia [ 42 , 43 ]. Insomnia is the most common sleep disturbance associated with anxiety disorders [ 34 ] and poor sleep quality is frequent in adults with anxiety disorders [ 44 ], who experience disturbances in the sleep-onset or sleep maintenance and insomnia. The association of insomnia and OSA is frequent (29.2%) and stands as a cumulative risk factor for cardiovascular diseases [ 45 ] while favoring arousal-inducing sleep-related behaviors, higher levels of pre-sleep arousal, anxiety, and depression more than OSA alone [ 46 ].…”
Section: Sleep-mental Health Interplaymentioning
confidence: 99%
“…High perceived stress, psychological distress, anxiety and depression are significant predictors of poor sleep quality and persistent insomnia [ 40 , 41 ] and can contribute to insomnia-related hyperarousal thus perpetuating chronic insomnia [ 42 , 43 ]. Insomnia is the most common sleep disturbance associated with anxiety disorders [ 34 ] and poor sleep quality is frequent in adults with anxiety disorders [ 44 ], who experience disturbances in the sleep-onset or sleep maintenance and insomnia. The association of insomnia and OSA is frequent (29.2%) and stands as a cumulative risk factor for cardiovascular diseases [ 45 ] while favoring arousal-inducing sleep-related behaviors, higher levels of pre-sleep arousal, anxiety, and depression more than OSA alone [ 46 ].…”
Section: Sleep-mental Health Interplaymentioning
confidence: 99%
“…Given that this study worked with the non-clinical and population-based sample, the reverse relationship (days of poor sleep as the independent variable and days of mental health problems as the dependent variable) may be plausible. Researchers have suggested that sleep deprivation can raise risk for or contribute to the development of various mental health disorders including depression, bipolar disorder, anxiety, schizophrenia, and cognitive impairment (Bao et al, 2017; da Silva, 2015; Harvard Health Publishing, n.d.; Kamath et al, 2015; Simon et al, 2016). It is considered that sleep disturbance influences the secretion of neurotransmitters and stress hormones and this may impair emotional regulation and the normal cognitive processes (Harvard Health Publishing, n.d., n.d; Yoo et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…GAD in patients with insomnia will generally have impact in feeling dissatisfied with the quantity and quality of sleep subjectively and objectively, could not feel refreshed and energized after awake. 22, 23 Moreover, sleep quality does not improve in GAD patients that are in remission. 4 Patients with panic disorder tend to have unexpected panic attacks during sleep and may increase sleep latency, decrease sleep duration, increase daytime sleepiness and sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Panic disorder is also commonly comorbid with depression. 4, 23 Social phobia has also a strong relationship with sleep quality, in which patients with social phobias tend to experience increase in sleep latency, sleep problems, and daytime dysfunction. 22 Baker, et al 5 stated anxiety patients often experience anxiety before going to sleep, anxiety and fear generates a fight or flight response that can interfere the sleep onset.…”
Section: Discussionmentioning
confidence: 99%